Estudo do mecanismo de inibição da PI3Kα e PI3Kδ e prospecção de compostos de origem vegetal com atividade inibitória seletiva/dual - Sousa, Francisca Joseli Freitas de (2022)
The PI3K/Akt/mTOR pathway plays a central role in cellular metabolism, regulating processes related to proliferation and survival. Alterations in PI3K activation are frequently linked to the development and progression of several types of cancer, including Diffuse Large B-cell Lymphoma (DLBCL). In this context, inhibition of PI3Kδ and PI3Kα is beneficial in the treatment of DLBCL, in which the PI3K pathway is overactive. In this work, we initially employed interaction energy quantum calculations to better understand the intermolecular influences that guide selective inhibition in PI3Kα and PI3Kδ isoforms, then used the acquired knowledge to assist during the identification of compounds with inhibitory potential via ensemble docking-based virtual screening. For the prospection of new molecules, we used the Brazilian natural products library (NuBBE) where only compounds with plant origin were analyzed. Our results indicate that for PI3Kδ the most attractive energies came from residues Trp760, Ile910, Met900, Ile825, Met750, and Tyr813, while for PI3Kα residues Val851, Ile848, Trp780, Tyr836, Val850, Ile932 interacted strongly with selective ligands. During the standardization step of the molecular docking technique, it was possible to identify the best composition of structural conformations, as well as the best parameters that enabled the identification of selective and dual inhibitors for PI3Kα and PI3Kδ isoforms. Among the compounds identified via virtual screening, 4-Deoxyraputindole C (NuBBE_1085), Raputindole B (NuBBE_1137), 11-decyl-11,12-dihydro-5,10-dioxatetraphen-12-one (NuBBE_1563), Glycocitrine-I (NuBBE_1074) (selective PI3Kδ), 3-(2-(7,7-dimethyl -3,7- dihydropyrano[3,2-e]indol-1-yl)ethyl-1-methylquinazoline-,4(1H,3H)-dione (NuBBE_ 1107), Podocarpusflavone A (NuBBE_199), Amentoflavone 7'',4'''-dimethyl-ether (NuBBE_198), Limonianin (NuBBE_1263), 9,10-Dihydro-9-hydroxy-9-(benzyloxycarbonylmethyl)-10-oxophe nanthrene (NuBBE_1368) (dual PI3Kδ/PI3Kα) and 3', 4'-dimethoxy-7,8-(2'',2''-dimethylpyrano)-flavanone (NuBBE_1327), Sesamin (NuBBE_ 1416), Vismiaquinone (NuBBE_2088), (+)-asarinin (NuBBE_1420), 6a,12a-dehydro-rotenone (NuBB_1451) (selective PI3Kα), stood out. The results obtained in this work may contribute to the rational development of new compounds with inhibitory potential on PI3Kα and PI3Kδ proteins and represent an important contribution for the elucidation of interactions between inhibitors and residues at the ATP-binding site of both enzymes.